PENGARUH PENDIDIKAN ISLAM DALAM KELUARGA TERHADAP KENAKALAN REMAJA DI SMPN 07 TELUK KUANTAN - Febi Pransiska; Andrizal Andrizal; Ikrima Mailani (Universitas Islam Kuantan Singingi, 2020)
The background of the researcher taking this title is that the researcher wants to know the effect of Islamic religious education in the family on juvenile delinquency in SMPN 07, Kuantan Bay. The formulation of the researcher's problem is how the influence of the influence of Islamic religious education in the family on juvenile delinquency in SMPN 07, Kuantan Bay. This research was conducted at SMPN 07 Kuantan Bay. Data collection techniques through interview studies, observation, documentation, questionnaires (questionnaire). And then the researchers analyzed the data using the Quantitative Method, data collection was carried out by submitting a questionnaire to respondents, namelystudents and parents of students at SMPN 07 Teluk Kuantan. The results showed that there was a significant influence between the variables of religious education in the family on juvenile delinquency. T test results there is a positive influence between Islamic religious education in the family of juvenile delinquency in SMPN 07, Kuantan Bay. This can be seen from the coefficient of determination of 0.61.3089 meaning that there is an influencebetween Islamic education in the family of adolescents' anger at SMPN 07, Kuantan Bay.While the T test has a positive influence between Islamic religious education in the family of juvenile delinquency in SMPN 07, Kuantan Bay. This can be seen from the value of Y = 25.502 + X 0.625 which means that Ho is rejected and Ha is accepted. Therefore there is an influence between Islamic religious education in the family of juvenile delinquency at SMPN 07, Kuantan Bay.